FLOUTS OF THE MAXIMS IN INTERVIEW BETWEEN BARRACK OBAMA AND ROBIN ROBERTS OF ABC NEWS "GOOD MORNING AMERICA," - Seftika, author (JURNAL SMART, 2015)
Cooperative principle plays an important role in communication. It is one of major principles which guide peopleâs communication. Itâs application in spoken is interested the researcher to analyze the flouting of cooperative principle maxims in Interview between president Barack Obama and Robin Roberts of ABC News "Good Morning America". This study aimed to find out which maxims are flouted in Barrack Obamaâs interview. In collecting the data, the researcher used documentation. Descriptive qualitative method was employed in processing the transcription data. It was analyzed using the theory of Griceâ s conversational maxims. Having analyzed the data. The write found the result that there are eighteen flouts of maxims which found in the interview. Based on the finding, it can be concluded that the flouting of maxims also occurred in formal communication such as in presidentâs interview. Moreover, the interviewee disobeyed these maxims for getting particular purposes.Key words: Cooperative principles; maxims; and flouting; interview